SECURITY MECHANISMS AND ANALYSIS FOR INSECURE DATA STORAGE AND UNINTENDED DATA LEAKAGE FOR MOBILE APPLICATIONS - Santana, Vanessa M.; Centonze, Paolina (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Using one mobile programming language like Objective-C, Swift or Java is challenging enough because of the many things that need to be considered from a security point of view, like the programming language secure guidelines and vulnerabilities. With the introduction of Swift in 2014 it’s now possible to build Swift/Objective-C mobile applications. Building a mobile application using two languages also adds a greater attack surface for hackers because of the need for developers to stay up to date on vulnerabilities on more than one language and operating system. To our best knowledge, since as of today, there is no academic-research based effort comparing Swift, Objective-C and Android from a programming language and platform security point of view. Our comparative analysis covers a subset of OWASP top ten mobile vulnerabilities and seeing how Swift, Objective-C and Android programming languages safeguard against these risks and how the built-in platform security mechanisms for Android and Apple for the chosen subset of OWASP vulnerabilities compare when placed side-by-side.